Quadratic equation, Mathematics

If roots of (x-p)(x-q) = c are a and b

what will be the roots of (x-a)(x-b) = -c please explain.

Solution)  (x-p)(x-q)=c

x2-(p+q)x-c=0

hence,   a+b=p+q

 and    a.b=pq-c

          a.b+c=p.q

by solving other eq we get

x2-(a+b)x+ab+c=0

thus  sum of roots=a+b=p+q

 product of roots=a.b+c=p.q

hence its roots are pand q

Posted Date: 3/9/2013 8:08:51 AM | Location : United States







Related Discussions:- Quadratic equation, Assignment Help, Ask Question on Quadratic equation, Get Answer, Expert's Help, Quadratic equation Discussions

Write discussion on Quadratic equation
Your posts are moderated
Related Questions
Which of the partially ordered sets in figures (i), (ii) and (iii) are lattices? Justify your answer.   Ans: suppose (L, ≤) be a poset. If each subset {x, y} consisting

Jack and his mother paid $11.50 for tickets to the movies, and adults tickets cost $4.50 more than a child ticket what was the cost of each ticket?

how to solve trignometric equations more easier?

Basic "computation" formulas : Next, let's take a quick look at some basic "computation" formulas that will let us to actually compute some derivatives. Formulas 1)   If f


Jon ran around a track that was one eighth of a mile long.He ran around the track twenty four times.How many miles did Jon run in all


Extended product rule : As a last topic let's note that the product rule can be extended to more than two functions, for instance.  ( f g h )′ = f ′ gh + f g ′ h+ f g h′ ( f

similar triangles diagram

the ratio of dogs to cats is 2 to 9.if there are 10 dogs how many cats are there?